Attitudes and Approaches Towards Repeat Valve Surgery in Recurrent Injection Drug Use-associated Infective Endocarditis: A Qualitative Study. Issue 3 (May 2020) - Hayden, Margaret; Moore, Amber
Abstract : Objective: The aim of this study was to explore the diversity of attitudes and approaches towards treating patients with recurrent injection drug use-associated infective endocarditis (IDU-IE) with a focus on surgical decision-making. Methods: Nineteeen qualitative, semistructured interviews were performed with healthcare providers at a single academic medical center. Purposive sampling was used to recruit participants with the goal of sampling a diversity of providers involved in the care of patients with IDU-IE. An inductive, grounded theory approach was used to analyze data. Results: Nineteen healthcare providers (12 physicians, 3 social workers, 2 registered nurses, 2 advanced practice providers) with experience caring for patients with IDU-IE across a variety of disciplines and departments participated in the study. Three themes emerged from the interviews: providers feel underprepared to care for patients with IDU-IE; implicit and explicit bias remain pervasive; and criteria for surgical decision-making are not transparent. When discussing surgical decision-making, participants relied on 2 predominant bioethical concepts: futility and rationing. Conclusions: There was a wide divergence of opinions on how to approach repeat valve surgeries, ranging from those who endorsed strict single surgery policies to those who felt patients should be offered as many surgeries as needed. Therefore, there is a need to further develop general principles for the care of recurrent IDU-IE to provide more reliable and equitable care to these patients. This will require input from an interdisciplinary group and should address empirical data, and also the appropriateness of futility and rationing of care questions. Abstract : Supplemental Digital Content is available in the text